(untitled) (Research, Society and Development, 2022)
Objective: To analyze the temporal trend and spatial distribution of mortality from fibrosis and liver cirrhosis (LC) in the state of Sergipe from 2001 to 2020. Methodology: Ecological time series study on mortality from fibrosis and LC, from the Information System on Mortality, stratified according to death by year, age group, sex, year of death and municipalities. The standardized mortality rates (SMR) were calculated, using them for trend analysis by the Joinpoint model and in the spatial one by the Kernel density estimator. Results: Over the 20 years, the state of Sergipe had a total of 1.532 deaths from fibrosis and LC. PMS showed an average of 7,12 deaths per 100,000 inhabitants with a predominance of males aged 40-59 years. The time trend of males, aged between 20-39 years (APV=-12,4%) and 40-59 years (APV=-6,1%) showed a reduction in PMS, (p<0.01) between 2001 to 2020. In females, the general trend in the 40-59 age group was a reduction (p<0.01) and above 80 years, from 2004-2020 (VPA=-5,8%). there was a decrease (p<0.001). The municipalities with the highest density of deaths from liver fibrosis and cirrhosis were Pedrinhas, Cumbe, Cedro de São João, Santa Rosa de Lima and Ilha das Flores. Conclusion: During the study period, the state of Sergipe showed a trend towards a reduction in the mortality rate from liver fibrosis and cirrhosis in both sexes, with the number of deaths being higher in males of working age.